Seasonal carbon fluxes from vegetation and soil in a Mediterranean non-tidal salt marsh - L. Carrasco-Barea; D. Verdaguer; M. Gispert; X. D. Quintana; H. Bourhis; L. Llorens (Biogeosciences)
Salt marshes are important ecosystems for carbon sequestration. However, while studies of atmospheric carbon exchange fluxes have broadly been performed in tidal salt marshes, they are scarce in non-tidal salt marshes. In this study we measured, throughout 1 year, instantaneous net carbon dioxide (CO2) exchange rates from four halophytes which are dominant species of their corresponding habitat (Sarcocornia fruticosa in a halophilous scrub, Halimione portulacoides and Elytrigia atherica in a salt meadow, and Salicornia patula in a glasswort sward) of a Mediterranean non-tidal salt marsh. Soil CO2 and methane (CH4) fluxes from these habitats were also measured. E. atherica, a perennial herbaceous species, showed the highest photosynthetic rates during the entire year, but S. patula, an annual succulent herb, also had remarkable photosynthetic rates in summer. Interestingly, the woody fraction of the two perennial shrubs, S. fruticosa and H. portulacoides, showed CO2 uptake during most of the daily measurements. Regarding the studied habitats, the halophilous scrub and the salt meadow showed higher soil CO2 emissions than the glasswort sward, and the overall emissions were higher than those reported for tidal salt marshes. Both soil absorption and emission of CH4 were detected. In particular, CH4 emissions were remarkably high, similar to those found in low-salinity marshes and, in general, higher than those reported for salt marshes with a high water table salinity. Soil mineralization quotients of the halophilous scrub and the salt meadow were lower than those measured at the glasswort sward, suggesting a higher soil carbon sequestration potential of the first two habitats.